Upaya Meningkatkan Self Efficacy melalui Bimbingan Kelompok - Solihin Solihin; Arifin Nur Budiono; Wahyuni Wahyuni (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2019)
Research on efforts to improve self efficacy student of class viii d through services one watch singing in response assistance would not only provide islamic junior high school mts al- malt or malt and meal discerning men will vanish or wuluhan the commencement of academic year 2017 / 2018 .. with the treatment respondents as many as 28 students .Data collection method that is used is identification observation and other of any economic indicators ,. Based on the results of from preliminary observations other of any economic indicators and set me free and more and they received way to the main databank with figures the percentage of the level of self afficacy students at the school as much as 50 % , percentage of 75 % . That is why it is to service delivery that the technical assistance would group of four can increase the size of the behavior self afficacy students at the school a class of viii d at mts al ma’arif malt or malt and meal discerning men will vanish or wuluhan the commencement of academic year 2017 / 2018 Keywords: Guidance Group , Self Efficacy